NUMERICAL SOLUTION FOR THE LINEAR MODEL OF WAVE GENERATION BY A BUMP USING THE FTBS METHOD AND THE LAX METHOD - Syahbudin Sani, Azis
An uniform flow enters a channel that has a bump on its bottom. The flow strength is described by parameter Froude number, F. The existance of bump will affect the profile of flow’s surface. The flow will hit the bump and causes the generation of wave which is consist of one peak and two dales. This process can be modeled by Boussinessq equation as shown by L.H. Wiryanto and Sudi Mungkasi in Appl. Math. Sci. (2014). A numerical approach is applied to the model using finite difference method, which are FTBS or Forward Time Backward Space method and The Lax method. The FTBS method can confirm well supercritical flow type only (F > 1). While The Lax method can confirm well the model for both of supercritical flow type (F > 1) and subcritical (F < 1).